KARAKTERISTIK SELF-EFFICACY GURU MATEMATIKA SMP DI KOTA SERANG - Hafsah Hafsah; Syamsuri Syamsuri; Jaenudin Jaenudin (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2020)
Learning mathematics is inseparable from how mathematics is taught in educational institutions, but also the success of a teacher in teaching. This means that the teacher's role is very important to influence students' success in learning. In the learning process a teacher must have confidence (self-efficacy) in order to achieve learning goals. The teacher is a profession of a person who has the duty to educate, to teach, to guide, to assess and to evaluate students in the process of growth and development of students in order to achieve learning goals. Self-efficacy to the teacher is a teacher's self-confidence in his ability to organize and run learning programs so that the success of teaching assignments is specific to certain material contexts and can affect student performance. The purpose of this study was to describe the characteristics of the self-Efficacy of junior high school mathematics teachers in Serang City. This type of research is qualitative research. The subjects of the study were junior high school mathematics teachers in Serang City. Data collection techniques in this study used observation, interviews and documentation. The interview instrument was modified from the General Self-Efficacy (GSE) instrument which consisted of 10 question items. The data that has been obtained is then analyzed using the constant comparative method. The results showed that there were characteristics of the self-efficacy of mathematics teachers in Serang City which could be grouped into 2 groups is  constructive groups and normative groups. Constructive groups are teachers who have high self-efficacy. While normative groups are teachers who have moderate self-efficacy.